Laurence A. Steinhardt papers - Steinhardt, Laurence A. (Laurence Adolph), 1892-1950.
Correspondence, letterbooks, articles, speeches, financial papers, business records, legal papers, and other papers relating to Steinhardt's career as U.S. ambassador to Canada, Czechoslovakia, Peru , the Soviet Union, Sweden, and Turkey. Correspondents include George V. Allen, Anthony Joseph Drexel Biddle, Joseph Edward Davies, James A. Farley, Loy W. Henderson, Cordell Hull, C. D. Jackson, Alfred A. Knopf, Ruth Bryan Owen, Franklin D. Roosevelt, Edward R. Stettinius, Jr., Arthur Hays Sulzberger, and Sumner Welles.
Lawyer, economist, and diplomat.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Allen, George V. -- 1903-1970 -- Correspondence; Biddle, Anthony Joseph Drexel, -- 1896-1961 -- Correspondence; Davies, Joseph Edward -- Correspondence; Farley, James A. -- 1888-1976 -- Correspondence; Henderson, Loy W. -- 1892-1986 -- Correspondence; Hull, Cordell, -- 1871-1955 -- Correspondence; Jackson, C. D. -- 1902-1964 -- Correspondence; Knopf, Alfred A., -- 1892-1984 -- Correspondence; Owen, Ruth Bryan, -- 1885-1954 -- Correspondence; Roosevelt, Franklin D. -- 1882-1945 -- Correspondence; Stettinius, Edward R. -- 1900-1949 -- Correspondence; Sulzberger, Arthur Hays, -- 1891-1968 -- Correspondence; Welles, Sumner, -- 1892-1961 -- Correspondence; Canada -- Foreign relations -- United States; Czechoslovakia -- Foreign relations -- United States; Peru -- Foreign relations -- United States; Soviet Union -- Foreign relations -- United States; Sweden -- Foreign relations -- United States; Turkey -- Foreign relations -- United States; Diplomatic and consular service, American -- Canada; Diplomatic and consular service, American -- Czechoslovakia; Diplomatic and consular service, American -- Peru; Diplomatic and consular service, American -- Soviet Union; Diplomatic and consular service, American -- Sweden; Diplomatic and consular service, American -- Turkey; United States -- Foreign relations -- 20th century; United States -- Foreign relations -- Canada; United States -- Foreign relations -- Czechoslovakia; United States -- Foreign relations -- Peru; United States -- Foreign relations -- Soviet Union; United States -- Foreign relations -- Sweden; United States -- Foreign relations -- Turkey; Diplomats; Economists; Lawyers